+0  
 
0
40
2
avatar

\(x + y + xy = 19, \quad y + z + yz = 29, \quad z + x + zx = 23\)

 

If x, y, and z are positive real numbers satisfying the system above, then find x, y, and z.

 Jun 21, 2020
 #1
avatar+21558 
+1

x + y + xy  =  19   --->   y + xy  =  19 - x   --->   y(1 + x)  =  19 - x   

   --->   y  =  (19 - x) / (x + 1)          [Equation #1]

 

y + z + yz  =  29   --->   y + yz  =  29 - z   --->   y(1 + z)  =  29 - z

   --->   y  =  (29 - z) / (z + 1)          [Equation #2]

 

z + x + xz  =  23   --->   x + zx  =  23 - z   --->   x(1 + z)  =  23 - z

   --->   x  =  (23 - z) / (z + 1)          [Equation #3]

 

Substituting Equation #3 into Equations #1:     

   y  =  (19 - x) / (x + 1)   --->   y  =  [ 19 - (23 - z) / (z + 1) ] / [ (23 - z) / (z + 1)  + 1 ]

 

Multiplying numerator and denominator by (z + 1)

                                       --->   y  =  [ 19(z + 1) - (23 - z) ] / [ (23 - z) + 1(z + 1) ]

                                       --->   y  =  [ 19z + 19 - 23 + z ] / [ 23 - z + z + 1 ]

                                       --->   y  =  [ 20z - 4 ] / [ 24 ]

                                       --->   y  =  (5z - 1) / 6         [Equation #4]

 

Setting Equation #2 and Equation #4 equal to each other:

                                           (29 - z) / (z + 1)  =  (5z - 1) / 6 

Cross-multiplying:                          6(29 - z)  =  (5z - 1)(z + 1)

                                                       174 - 6z  =  5z2 + 5z - z + 1

                                                                  0  =  z2 + 2z - 35

                                                                  0  =  (z + 7)(z - 5)

 

So:  either  z = -7  or  z = 5        (the problem specifies that z must be positive   --->   z = 5)

 

 

Equation #2:  y  =  (29 - z) / (z + 1)   --->   y  =  (29 - z) / (5 + 1)   --->   y = 4

 

Equation #3:  x  =  (23 - z) / (z + 1)   --->   x  =  (23 - 5) / (5 + 1)   --->   x = 3  

 Jun 22, 2020
 #2
avatar+25247 
+2

If x, y, and z are positive real numbers satisfying the system above, then find x, y, and z.
\(x + y + xy = 19, \quad y + z + yz = 29, \quad z + x + zx = 23\)

 

\(\begin{array}{|rcll|} \hline \mathbf{x + y + xy} &=& \mathbf{19} \\ x (1+y)+ y &=& 19 \\ x (1+y)+ y+1-1 &=& 19 \\ x (1+y)+ (1+y) &=& 20 \\ \mathbf{(1+y)(1+x)} &=& \mathbf{20}\quad (1) \\ \hline \end{array} \begin{array}{|rcll|} \hline \mathbf{y + z + yz } &=& \mathbf{29} \\ y (1+z)+ z &=& 29 \\ y (1+z)+ z+1-1 &=& 29 \\ y (1+z)+ (1+z) &=& 30 \\ \mathbf{(1+z)(1+y)} &=& \mathbf{30}\quad (2) \\ \hline \end{array} \begin{array}{|rcll|} \hline \mathbf{z + x + zx } &=& \mathbf{23} \\ z (1+x)+ x &=& 23 \\ z (1+x)+ x+1-1 &=& 23 \\ z (1+x)+ (1+x) &=& 24 \\ \mathbf{(1+x)(1+z)} &=& \mathbf{24}\quad (3) \\ \hline \end{array}\)

 

\(\begin{array}{|lrcll|} \hline \dfrac{(1)*(3)}{(2)}: & \dfrac{(1+y)(1+x)(1+x)(1+z)} {(1+z)(1+y)} &=& \dfrac{20*24}{30}\\ &&& 1+z \ne 0,\ \text{respectively}\ z\ne-1 \\\\ &&& 1+y \ne 0,\ \text{respectively}\ y\ne-1 \\\\ & (1+x)(1+x)^2 &=& \dfrac{20*24}{30} \\ & (1+x)^2 &=& 16 \\ & 1+x &=& 4 \quad | \quad x > 0 !\\ & \mathbf{x} &=& \mathbf{3} \\ \hline \end{array} \)

 

\(\begin{array}{|lrcll|} \hline \dfrac{(2)*(1)}{(3)}: & \dfrac{(1+z)(1+y)(1+y)(1+x) } {(1+x)(1+z) } &=& \dfrac{30*20}{24} \\ &&& 1+x \ne 0,\ \text{respectively}\ x\ne-1 \\\\ &&& 1+z \ne 0,\ \text{respectively}\ z\ne-1 \\\\ & (1+y)(1+y)^2 &=& \dfrac{30*20}{24} \\ & (1+y)^2 &=& 25 \\ & 1+y &=& 5 \quad | \quad y > 0 !\\ & \mathbf{y} &=& \mathbf{4} \\ \hline \end{array}\)

 

\(\begin{array}{|lrcll|} \hline \dfrac{(3)*(2)}{(1)}: & \dfrac{(1+x)(1+z)(1+z)(1+y)} {(1+y)(1+x)} &=& \dfrac{24*30}{20} \\ &&& 1+y \ne 0,\ \text{respectively}\ y\ne-1 \\\\ &&& 1+x \ne 0,\ \text{respectively}\ x\ne-1 \\\\ & (1+z)(1+z)^2 &=& \dfrac{24*30}{20} \\ & (1+z)^2 &=& 36 \\ & 1+z &=& 6 \quad | \quad z > 0 !\\ & \mathbf{z} &=& \mathbf{5} \\ \hline \end{array}\)

 

 

laugh

 Jun 22, 2020

8 Online Users

avatar